THE CORRELATION BETWEEN VOCABULARY MASTERY AND WRITING ABILITY OF THE THIRD YEAR STUDENTS OF ENGLISH STUDY PROGRAM OF FKIP UNIVERSITAS RIAU - Agustina, Rahmasari; Novitri, Novitri; Syarfi, Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is aimed to find out the significant correlation between vocabulary mastery and writing ability of the third year students of English Study Program FKIP Universitas Riau. The sample of this research was class 6B, consisting of 35 students. The data were collected using two kinds of test; namely, a vocabulary test and writing test. The result of this research showed the third year students of English Study Program FKIP Universitas Riau achieved good level in both vocabulary and writing with the average score 77 in vocabulary and 67 in writing. The result of this research proved that there was a positive correlation between the vocabulary mastery and writing ability of the third year students of English Study Program FKIP Universitas Riau. The Rxy distribution of the coefficient correlation was 0.541. It means that there was a fair correlation between vocabulary mastery and writing ability of the third year students of English Study Program FKIP Universitas Riau. Therefore, the null hypothesis (Ho) was rejected and alternative hypothesis (Hα) was accepted.Key Words: Correlation, Vocabulary Mastery, Writing Ability